2014
DOI: 10.2355/isijinternational.54.304
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Unsteady Molten Steel Flow and Inclusion Behavior in the Tundish in the Ladle Change Period

Abstract: Prevention of defects caused by inclusions is an important technical issue in the production of highgrade steel products. In particular, inclusion removal in the continuous casting tundish is an essential technology for production of high-grade steels. It is well known that inclusion removal in the ladle change period is more difficult than during steady state casting. However, the unsteady phenomena of molten steel flow and inclusion motion in the ladle change period have not been studied in detail. To clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Therefore, in order to conduct the research study on the flow fields and also on the parameters to set the mould oscillation rate, there are applied determined laboratory and mathematical models, which constitute the basis for numerical modelling. [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to conduct the research study on the flow fields and also on the parameters to set the mould oscillation rate, there are applied determined laboratory and mathematical models, which constitute the basis for numerical modelling. [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…At present, most numerical investigations of the tundish have only considered the steady casting process using flow field modeling. Simulations of transient casting [6][7][8][9][10][11][12][13] are still only rarely undertaken. Takahashi et al [7] simulated the velocity field in slab tundish during the ladle change, and provided a basis for predicting the change of the floating condition of inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous inclusions mainly generated due to re-oxidation in tundish, slag entrapment, lining erosions which have detrimental effect on cast structure and to control this adverse effect on product state of art technology is required to develop for future sustainability [41]. Numerical simulation was applied by some researchers to evaluate the inclusion characteristics during ladle change over period and it was found that during this unsteady state inclusion percentage in the tundish as well as mold increases and also it is inferred that proper flow control device can enhance the inclusion removal rate in tundish during opening of new ladle in a sequence casting operation as clean steel is highly desirable for particularly high grade steel casting [42]. So it is highly desirable to judge the inclusion removal efficiency of different types shroud and impact pad combinations.…”
Section: Inclusion Floatation Characteristics For Different Shroudmentioning
confidence: 99%